2022
DOI: 10.5853/jos.2022.01102
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Therapy Response in Chronic Aphasia: Building a Foundation for Personalized Aphasia Therapy

Abstract: Chronic aphasia, a devastating impairment of language, affects up to a third of stroke survivors. Speech and language therapy has consistently been shown to improve language function in prior clinical trials, but few clinicially applicable predictors of individual therapy response have been identified to date. Consequently, clinicians struggle substantially with prognostication in the clinical management of aphasia. A rising prevalence of aphasia, in particular in younger populations, has emphasized the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 218 publications
3
12
0
Order By: Relevance
“…Aphasia severity . Aphasia severity is commonly recognized as an influential factor for language recovery (e.g., Kristinsson et al, 2022 ; Plowman et al, 2012 ; Watila & Balarabe, 2015 ). The cortical organization of language relies on dynamic interactions across temporal, parietal, and frontal brain regions ( Hickok & Poeppel, 2007 ; Tourville & Guenther, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aphasia severity . Aphasia severity is commonly recognized as an influential factor for language recovery (e.g., Kristinsson et al, 2022 ; Plowman et al, 2012 ; Watila & Balarabe, 2015 ). The cortical organization of language relies on dynamic interactions across temporal, parietal, and frontal brain regions ( Hickok & Poeppel, 2007 ; Tourville & Guenther, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it would be reasonable to expect limited language recovery in older PWA. Indeed, there are studies that have found that people that experience aphasia at a younger age tend to have better outcomes in comparison to people that manifest aphasia at older ages e.g., [ 93 , 94 ]. Nevertheless, the association between age and recovery varies between studies [ 95 , 96 ] and this variation may be attributed to several factors (e.g., comorbidities, differences in sample characteristics and assessment methods).…”
Section: Can We Predict Which Pwa Will Respond To Treatment?mentioning
confidence: 99%
“…For example, given the complex dynamics of recovery after stroke, 3 a right hemisphere activation in an aphasic patient after a left infarct could reflect a pre‐stroke atypical language representation or could result from a post‐stroke inter‐hemispheric shift of language systems. Ideally, a within‐patient comparison between pre‐ and post‐deficit neuroimaging data would provide a much accurate depiction of brain re‐organization mechanisms, which can ultimately support the design of personalized therapies 4 . We are ushering into a new era that might make this a possibility in the light of the exponential growth in the number of participants in neuroimaging research.…”
Section: Individualized Depiction Of Post‐deficit Outcome and Recoverymentioning
confidence: 99%
“…Ideally, a within-patient comparison between pre-and post-deficit neuroimaging data would provide a much accurate depiction of brain re-organization mechanisms, which can ultimately support the design of personalized therapies. 4 We are ushering into a new era that might make this a possibility in the light of the exponential growth in the number of participants in neuroimaging research. Indeed, thousands of neurotypical volunteers are tested every year, mainly for research purposes, but their brain scans can soon help address other questions related to brain changes and re-organization in a novel and reliable way based on within-subject comparisons.…”
Section: Individualized Depiction Of Post-deficit Outcome and Recoverymentioning
confidence: 99%